2012
DOI: 10.1016/j.rbmo.2012.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adenomyosis on implantation

Abstract: Reproductive BioMedicine Online (2012) 24, 584 w w w . s c i e n c e d i r e c t . c o m w w w . r b m o n l i n e . c o m

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…In addition, in individuals with adenomyosis, no differences were observed in genes relevant for implantation (Martínez-Conejero et al, 2011), but the latter study did not control for the various down-regulation protocols. Their term pregnancy rate (84% of clinical pregnancies) for the control group is remarkable, compared with 76% in the group with adenomyosis (Martínez-Conejero et al, 2011;Vila-Vives et al, 2012). In conclusion, at present it cannot be ruled out that defects in implantation or in mechanisms relevant to embryo selection may play a role (Koot et al, 2012;Salker et al, 2012).…”
Section: Adenomyosis and Infertilitymentioning
confidence: 77%
“…In addition, in individuals with adenomyosis, no differences were observed in genes relevant for implantation (Martínez-Conejero et al, 2011), but the latter study did not control for the various down-regulation protocols. Their term pregnancy rate (84% of clinical pregnancies) for the control group is remarkable, compared with 76% in the group with adenomyosis (Martínez-Conejero et al, 2011;Vila-Vives et al, 2012). In conclusion, at present it cannot be ruled out that defects in implantation or in mechanisms relevant to embryo selection may play a role (Koot et al, 2012;Salker et al, 2012).…”
Section: Adenomyosis and Infertilitymentioning
confidence: 77%
“…Also the potential effect of adenomyosis on implantation has been debated recently. Whereas Campo et al (2012a,b) hypothesized a detrimental impact mediated by perturbed uterine peristalsis and reduced endometrial receptivity indicated by the presence of implantation marker defects, Martínez-Conejero et al (2011) and Vila-Vives et al (2012) reported no statistically significant differences in implantation and pregnancy rates between women with or without adenomyosis diagnosed at TVUS. However, if adenomyosis is considered a uterine factor of infertility, it seems logical to infer that impaired implantation constitutes the pathogenic mechanism leading to reduced clinical pregnancy rate.…”
Section: Figurementioning
confidence: 99%
“…The association between infertility and endometriosis and adenomyosis (10) has been widely studied (11). It is known that eutopic endometrium is altered in women with endometriosis (12), and that it diminishes endometrial receptivity and embryo implantation (13), but the mechanistic link remains unknown.…”
mentioning
confidence: 99%